Enlargement of occurrence area of Drosophila suzukii (Diptera, Drosophilidae) in Santa Catarina, Brazil - Zazycki, Luiza Cristiane Fialho; Vargas, Julia Patricia; Bonfim, Vanessa Santana; Garcia, Flávio Roberto Mello (Revista de Ciências Agroveterinárias, 2019)
The spotted wing Drosophila has significant economy relevance due to attacking thin epicarp fruits, which have high commercial value, mainly for “in natura” consumption. The Brazilian pest reports to date are distributed in the states of Rio Grande do Sul, Santa Catarina, Paraná, São Paulo, Rio de Janeiro, Goiás, and Minas Gerais. Our study aimed to record the enlargement of occurrence area of this species in the Serrana region of Santa Catarina. For this, traps PET type baited with apple cider vinegar in an organic strawberry crop in a semi-hydroponic system in the municipality Frei Rogério. Traps monitored 8.600 plants for ten days, and the collected material was evaluated with a stereoscopic microscope. Several insects of Drosophilidae family were collected, of which ninety-eight females and four males of Drosophila suzukii, thus revealing the enlargement of pest presence in the Serrana region of Santa Catarina.